PENINGKATAN KEMAMPUAN MATEMATIKA PESERTA DIDIK MELALUI CERDAS CERMAT JENJANG SD DAN SMP DI KECAMATAN HUAMUAL KABUPATEN SERAM BAGIAN BARAT - Ahmad Salatalohy; Halima Bugis; Ahmad Alwi; Asria Ratau; Ismail Borut; Arien Sayang; Sarifa Sarifa; Windi Samaneri; Wa Nurmin Wagola; Wa Samuria Wally; Urusia Indriani Aineka (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This activity aims to improve the mathematical skills of students through quiz activities for the SD/MI and SMP/MTs levels located in huamual sub-district of western Seram district. The participants who participated in this meticulous smart activity were eight teams for each level. The implementation of smart activities is divided into two rounds, namely the preliminary round and also the final round. For participants who are able to get the highest score in the final round, they become champions in quiz activities. Based on the score, the first winner in the SD/MI level quiz activity was the B team from the Muhammadiyah Telaga MI school, while the SMP/MTs level was won by the C team from Muhammadiyah Temi Junior High School. This activity not only won a champion from each level, but more importantly was able to improve mathematical skills, self-confidence, and motivation for each competition participant who participated in it.